ImmunoPET Imaging of TIM‐3 in Murine Melanoma Models. Issue 7 (17th April 2020) - Wei, Weijun; Jiang, Dawei; Lee, Hye Jin; Engle, Jonathan W.; Akiba, Hisaya; Liu, Jianjun; Cai, Weibo
Abstract: T cell immunoglobulin and mucin domain‐containing‐3 (TIM‐3) is an immune checkpoint expressed mainly on CD4 + and CD8 + T cells. In addition to negatively regulating inflammatory T cell function, TIM‐3 is a promising immunotherapy target. Herein, the aim is to develop an immuno‐positron emission tomography (immunoPET) probe for noninvasively characterizing TIM‐3 expression. Flow cytometry is used to detect the expression levels of TIM‐3 in B16F10 cells. RMT3‐23, a rat antimouse TIM‐3‐specific monoclonal antibody, is radiolabeled with 64 Cu and the performance of 64 Cu‐NOTA‐RMT3‐23 is interrogated by immunoPET in murine melanoma models before and after radiation therapies. Biodistribution and immunofluorescent staining studies are carried out after the immunoPET imaging studies. TIM‐3 is negatively expressed in B16F10 cells, and its expression is not induced by radiation therapies. ImmunoPET imaging with 64 Cu‐NOTA‐RMT3‐23 precisely tracks the unique distribution of TIM‐3‐positive lymphocytes in immunocompetent melanoma models, and tumor uptake of the radiotracer is not affected by either single‐dose or fractionated radiation therapies. The 64 Cu‐NOTA‐RMT3‐23 immunoPET imaging results are further mirrored by the immunofluorescent staining studies. These results demonstrate the feasibility of 64 Cu‐NOTA‐RMT3‐23 immunoPET in tracking TIM‐3 and highlight a new opportunity to optimize TIM‐3‐targeted immunotherapies with this novel imaging strategy. Abstract : T cell immunoglobulin and mucin domain‐containing‐3 (TIM‐3) is an immune checkpoint expressed mainly on CD4 + and CD8 + T cells. In addition to negatively regulating inflammatory T cell function, TIM‐3 also contributes to the immunosuppressive tumor milieu and is a promising immunotherapy target. This work develops a TIM‐3‐specific radiotracer 64 Cu‐NOTA‐RMT3‐23 and immuno‐positron emission tomography imaging with this agent efficiently characterizes the dynamics of TIM‐3 in murine melanomas.